Two-year post-discharge costs of care among patients treated with transcatheter or surgical aortic valve replacement in Germany - Klaus Kaier; Frederike von Kampen; Hardy Baumbach; Constantin von zur Mühlen; Philip Hehn; Werner Vach; Manfred Zehender; Christoph Bode; Jochen Reinöhl (BMC, 2017)
Abstract Background This study presents data on post-discharge costs of care among patients treated with transcatheter or surgical aortic valve replacement over a two year period. Methods Based on a prospective clinical trial, post-discharge utilization of health services and status of assistance were collected for 151 elderly patients via 2250 monthly telephone interviews, valued using standardized unit costs and analysed using two-part regression models. Results At month 1 post-discharge, total costs of care are substantially elevated (monthly mean: €3506.7) and then remain relatively stable over the following 23 months (monthly mean: €622.3). As expected, the majority of these costs are related to in-hospital care (~98% in month 1 post-discharge and ~72% in months 2-24). Patients that died during follow-up were associated with substantially higher cost estimates of in-hospital care than those surviving the two-year study period, while patients' age and other patient characteristics were of minor relevance. Estimated costs of outpatient care are lower at month 1 than during the rest of the study period, and not affected by the event of death during follow-up. The estimated costs of nursing care are, in contrast, much higher in year 2 than in year 1 and differ substantially by gender and type of procedure as well as by patients' age. Overall, these monthly cost estimates add up to €10,352 for the first and €7467.6 for the second year post-discharge. Conclusions Substantial cost increases at month 1 post-discharge and in case of death during follow-up are the main findings of the study, which should be taken into account in future economic evaluations on the topic. Application of standardized unit costs in combination with monthly patient interviews allows for a far more precise estimate of the variability in post-discharge health service utilization in this group of patients than the ones given in previous studies. Trial registration German Clinical Trial Register Nr. DRKS00000797 .